PENGARUH PENGETAHUAN KEWIRAUSAHAAN, KECUKUPAN MODAL DAN MODAL SOSIAL TERHADAP KEPERCAYAAN DIRI DAN PRODUKTIVITAS PENGUSAHA UMKM TEKSTIL DI DESA ADAT KUTA KABUPATEN BADUNG - Saraswati, Ni Luh Putu Lani; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 7 (2020): VOL 9 NO 7, JULI 2020 (1431-1630), 2020)
The purpose of this study is (1) to analyze the direct influence of entrepreneurial knowledge, capital adequacy and social capital on the confidence of textile SME entrepreneurs in Kuta Adat Village, Badung Regency, (2) analyze the direct effect of entrepreneurial knowledge, capital adequacy, social capital and self-confidence in productivity of textile MSME entrepreneurs in the Kuta Adat Village of Badung Regency, and (3) analyzing the indirect effect of entrepreneurial knowledge, capital adequacy and social capital on productivity through the confidence of the textile MSME entrepreneurs in the Kuta Adat Village of Badung Regency. The data used are primary data with a sample of 89 workers. The method of determining the sample by using the method of proposiveate stratified random sampling. The analysis technique used is the path analysis technique (path analysis). The results showed that entrepreneurship knowledge, capital adequacy and social capital had a direct effect on the confidence of textile SME entrepreneurs in Kuta Adat Village, Badung Regency. Knowledge of entrepreneurship, capital adequacy, social capital and self-confidence directly influence the productivity of textile SME entrepreneurs in the Adat Kuta Village of Badung Regency. Self-confidence mediates the effect of entrepreneurial knowledge, capital adequacy and social capital on the productivity of textile MSME entrepreneurs in Kuta Adat Village, Badung Regency. Keywords : entrepreneurial knowledge, venture capital, social capital, self-confidence, and productivity